SOCIAL DEVELOPMENT SUSTAINABILITY AMID THE GLOBAL ECONOMIC CRISIS - Loso Judijanto; Iwan Kusnadi (CV. Adiba Aisha Amira, 2024)
Social Development Sustainability Amid the Global Economic Crisis is the ability of a country or society to maintain and continue efforts to improve social welfare, quality of life, and equitable access to basic services, despite facing significant global economic challenges. This concept includes efforts to maintain the stability of social programs, ensure protection for vulnerable groups, and develop adaptive strategies that enable sustainable social progress, even when economic resources are limited or unstable. Social development sustainability in this context also involves innovations in service delivery, strengthening community resilience, and integrating economic, social, and environmental aspects to create a more resilient system in the face of global economic shocks. The research method in this study uses literature. The results show that while the global economic crisis has worsened inequality and strained social protection systems, it has also encouraged innovation in social service provision and reinforced the importance of investing in sustainable social development.